THE IMPLEMENTATION OF THE RECIPROCAL TEACHING LEARNING MODEL TO IMPROVE MATHEMATICS CREATIVE THINKING ABILITY OF JUNIOR HIGH SCHOOL STUDENTS - Mirnalisa Mirnalisa; Zainal Abidin; Muhammad Yani (Prodi Tadris Matematika Universitas Muhammadiyah Aceh, 2021)
Mathematical creative thinking ability is one of the abilities that must be possessed by students in studying mathematics. This is because the ability to think creatively can train students in designing various kinds of solutions in solving a problem. However, in reality, students' mathematical creative thinking skills are still relatively low, so a learning model is needed that can improve students' mathematical creative thinking skills. The purpose of this study was to determine (1) the improvement of students' mathematical creative thinking skills after receiving learning using reciprocal teaching and conventional learning models in class VIII SMPN 1 Baitussalam and (2) the level of students' mathematical creative thinking after applying the reciprocal teaching learning model in class VIII SMPN 1 Baitussalam. The research method used is an experimental method with a control group pretest posttest design. The population in this study were all students of class VIII SMPN 1 Baitussalam with the sample taken by simple random sampling. The selected samples were students of class VIII-B as the experimental class and students of class VIII-C as the control class. Data were collected using a mathematical creative thinking ability test sheet which was then analyzed using the right-hand t-test and n-gain. The results showed that (1) the improvement of students' mathematical creative thinking skills after receiving learning with the reciprocal teaching model was better than conventional learning in class VIII of SMPN 1 Baitussalam. (2) the level of students' mathematical creative thinking ability after learning with the reciprocal teaching model is in the